1-Deoxysphingolipid-induced neurotoxicity involves N-methyl-d-aspartate receptor signaling. (November 2016) - Güntert, Tanja; Hänggi, Pascal; Othman, Alaa; Suriyanarayanan, Saranya; Sonda, Sabrina; Zuellig, Richard A.; Hornemann, Thorsten; Ogunshola, Omolara O.
Abstract: 1-Deoxysphingolipids (1-deoxySL) are atypical and neurotoxic sphingolipids formed by alternate substrate usage of the enzyme serine-palmitoyltransferase. Pathologically increased 1-deoxySL formation causes hereditary sensory and autosomal neuropathy type 1 (HSAN1) - a progressive peripheral axonopathy. However, the underlying molecular mechanisms by which 1-deoxySL acts are unknown. Herein we studied the effect of 1-deoxysphinganine (1-deoxySA) and its canonical counterpart sphinganine (SA) in aged cultured neurons comparing their outcome on cell survival and cytoskeleton integrity. 1-deoxySA caused rapid neuronal cytoskeleton disruption and modulated important cytoskeletal regulatory and associated components including Rac1, Ezrin and insulin receptor substrate 53. We show that 1-deoxySA is internalized and metabolized downstream to 1-deoxydihydroceramide since inhibition of ceramide synthase protected neurons from 1-deoxySA-mediated cell death. In addition, 1-deoxySA reduced protein levels of N-methyl-d -aspartate receptor (NMDAR) subunit GluN2B, the postsynaptic density protein 95 and induced cleavage of p35 to p25. Notably, blocking NMDAR activation by MK-801 or memantine significantly prevented 1-deoxySA neurotoxicity. Functional studies of differentiating primary neurons via the patch-clamp technique demonstrated that 1-deoxySA irreversibly depolarizes the neuronal membrane potential in an age-dependent manner. Notably, only neuronal cells that displayed functional NMDAR- and NMDA-induced whole-cell currents responded to 1-deoxySA treatment. Furthermore, pre-exposure to the non-competitive antagonist MK-801 blocked the current response of NMDA and glycine, as well as 1-deoxySA. We conclude that 1-deoxySA-induced neurotoxicity compromises cytoskeletal stability and targets NMDAR signaling in an age-dependent manner. Thus stabilization of cytoskeletal structures and/or inhibition of glutamate receptors could be a potential therapeutic approach to prevent 1-deoxySA-induced neurodegeneration. Highlights: 1-deoxysphinganine (1-deoxySA) triggers neuronal cytoskeletal alterations and deregulation of associated proteins. 1-deoxySA activates the N-methyl-D-aspartate receptor (NMDAR) but down regulates GluN2B and PSD-95 expression. 1-deoxySA-induced neurotoxicity can be prevented via NMDAR inhibition or blocking ceramide synthesis. Cytoskeletal stabilization and/or glutamate receptor inhibition may potentially prevent 1-deoxySA-induced neurodegeneration.